Putting Standing to Work: Does Hypocrisy Undermine a Supervisor’s Moral Standing to Blame Employees? - Fritz, Kyle G. (Journal of business ethics, 2026)
Supervisors and managers plausibly have the moral standing, or right, to blame their employees for violations of company policies. Yet hypocrites plausibly lack the standing to hold others accountable for wrongs they are guilty of themselves. These two observations raise a concern: does a supervisor have the standing to blame their employees for violations of some company policy if the supervisor hypocritically also violates that policy? On one hand, it seems clear that they must, given their position in the company. On the other hand, it seems clear that they cannot, given their hypocrisy. We argue for a disjunctive explanation for this apparent inconsistency according to which hypocritical supervisors may lack standing qua individual persons, but nevertheless have standing either in virtue of their role or in virtue of inheriting the standing of their organization as a proxy for that organization. While the role solution is attractive in its simplicity, it is unclear that it can adequately explain all cases of hypocritical supervisors. Yet while the proxy solution is more complete, it relies on contentious claims about corporate moral responsibility. We develop both explanations, remaining neutral on whether the comprehensiveness of the proxy solution is worth its metaphysical commitments.